Experiences on grid shared data programming. (19th August 2009) - Tudor, Dacian; Macariu, Georgiana; Schreiner, Wolfgang; Cretu, Vladimir-Ioan
Despite the continuous advances of the last years in grid computing, programming paradigms are dominated by the message passing concept. There is little support for other paradigms such as shared data or associative programming. In this paper, we analyse why previous attempts did not have a significant impact in the grid computing community. We start by assessing the landscape of grid programming solutions with a focus on shared data concepts. Next, we introduce an original idea to attack shared data programming on the grid by making use of both relaxed consistency models and user specified type consistency in an object-oriented model. Last but not least, we present a prototype architecture together with experimental results.